Reliability and validity of angle measurements using radiograph and smartphone applications: experimental research on protractor - Enoki, Taisuke; Morikita, Ikuhiro; Awatani, Takenori (Journal of Physical Therapy Science, 2017)
[Purpose] The present study aimed to demonstrate the following by using measurements for the definite angles provided by the digital protractor: inter-rater reliability and validity in radiograph measurements and smartphone application measurements. [Subjects and Methods] The subject angles were 26 angles between 15° and 180° that were selected randomly using a computer. Three examiners measured the angles using the radiograph and smartphone application. The radiograph was obtained at a position 250 cm from the chest shooting cassette holder. The smartphone photograph was obtained at positions 50, 100, 150, 200, and 250 cm from the holder. [Results] Under all conditions, intra-class correlation coefficients showed 0.999. The correlation coefficient was 0.999 for all conditions. The mean absolute difference to the protractor was ≤0.28° for all conditions. [Conclusion] In comparison with the protractor, radiograph measurements and smartphone application measurements, the results of the present study showed high inter-rater reliability, validity, and small error. The results indicated that radiograph and smartphone application measurements could be used as criteria of validity in angle measurements. It supported the legitimacy of high-quality previous studies that used radiograph measurements as a criterion for validity.